Investigation of the relationship between incidence of mental disorders and economic growth among the Visegrad countries - Szőllősi, Gergő József; Boruzs, Klára; Karcagi-Kováts, Andrea; Kalas, Nándor; Bányai, Gábor; Bíró, Klára (Frontiers in Public Health, 2022)
Prevention and care for mental disorders represent an important public health task in achieving global development goals. Proper access to adequate healthcare and social services is an important step related to care for mental disorders, which is presumably strongly related to economic growth. The main aim of the study was to investigate the relationship between the economic growth and the incidence of mental disorders in the V4 countries. An ecological correlation study was conducted regarding the four Visegrad countries. Indicators were derived from the World Health Organization (WHO) ‘Health for All’ (HFA) online database and Penn World Table version 10. The incidence of mental disorders increased in the V4 countries throughout the years between 2000-2018 except in Hungary, where a decreasing trend was observed. The prevalence of mental disorders increased in all countries as well, but it stagnated in Hungary. At the same time standardized death rate due to mental disorders increased in all Visegrad countries. According to the Hungarian data, while the prevalence of the disease did not change remarkably, the incidence decreased and the mortality increased as well as the prescription of drugs used in the treatment of mental disorders. This could indicate a serious hidden morbidity.